Interdental papilla recession and reconstruction of the lost triangle: a review of the current literature - Barakat, Sanabel O. (Frontiers in Dental Medicine, 2025)
Interdental papilla (IDP) deficiency and the presence of gingival black triangles (GBT) are major concerns for both patients and dentists, as the IDP plays an important role in esthetics due to its strong association with the patient's smile. Interdental papilla deficiency is frequent among different populations, with a tendency to increase with age and in patients with periodontal disease. In addition, GBT causes phonetic problems, food impaction, plaque accumulation, and increased risk for root caries. The small dimensions of the IDP and the limited vascular supply to the interproximal space render treatment modalities of receded papillae unpredictable. Still, and based on the etiological factors, several non-surgical treatment options, including correction of traumatic oral hygiene practices, restorative interventions, papilla priming, papilla enhancement with either autologous fibroblast injection or hyaluronic acid, and orthodontic therapy, have been proposed to fill the GBT. In addition, different surgical techniques—with or without grafting biomaterials—have also been introduced to reconstruct the lost papilla. Nonetheless, there is no gold standard set yet. Further, systematic reviews evaluating the efficacy of surgical reconstruction of deficient IDP are still lacking due to the scarcity of large-scale clinical trials and the absence of long-term clinical outcomes. The aim of this review was to identify various causes of IDP recession as well as to explore the available treatment modalities to reconstruct the lost papilla.